Anabolic steroids reduce spinal cord injury-related bone loss in rats associated with increased Wnt signaling. (November 2013) - Sun, Li; Pan, Jiangping; Peng, Yuanzhen; Wu, Yong; Li, Jianghua; Liu, Xuan; Qin, Yiwen; Bauman, William A.; Cardozo, Christopher; Zaidi, Mone; Qin, Weiping
Abstract : Background: Spinal cord injury (SCI) causes severe bone loss. At present, there is no practical treatment to delay or prevent bone loss in individuals with motor-complete SCI. Hypogonadism is common in men after SCI and may exacerbate bone loss. The anabolic steroid nandrolone reduces bone loss due to microgravity or nerve transection. Objective: To determine whether nandrolone reduced bone loss after SCI and, if so, to explore the mechanisms of nandrolone action. Methods: Male rats with complete transection of the spinal cord were administered nandrolone combined with a physiological replacement dose of testosterone, or vehicle, beginning on day 29 after SCI and continued for 28 days. Results: SCI reduced distal femoral and proximal tibial bone mineral density (BMD) by 25 and 16%, respectively, at 56 days. This bone loss was attenuated by nandrolone. In ex vivo osteoclasts cultures, SCI increased mRNA levels for tartrate-resistant acid phosphatase (TRAP) and calcitonin receptor; nandrolone-normalized expression levels of these transcripts. In ex vivo osteoblast cultures, SCI increased receptor activator of NF-kB ligand (RANKL) mRNA levels but did not alter osteoprotegerin (OPG) mRNA expression; nandrolone-increased expression of OPG and OPG/RANKL ratio. SCI reduced mRNA levels of Wnt signaling-related genes Wnt3a, low-density lipoprotein receptor-related protein 5 (LRP5), Fzd5, Tcf7, and ectodermal-neural cortex 1 (ENC1) in osteoblasts, whereas nandrolone increased expression of each of these genes. Conclusions: The results demonstrate that nandrolone reduces bone loss after SCI. A potential mechanism is suggested by our findings wherein nandrolone modulates genes for differentiation and activity of osteoclasts and osteoblasts, at least in part, through the activation of Wnt signaling.